Current Status of Hepatocellular Carcinoma in Japan and Percutaneous Hot Ethanol Injection Therapy - NAKAI, MOTOKI; KISHI, KAZUSHI; SATO, MORIO; MASUDA, MITSUNORI; TANIHATA, HIROHIKO; TERADA, MASAKI; IWAMOTO, TAKUYA; KAWAI, NOBUYUKI; TAKEUCHI, TAIZO; ISHII, SEIGO (Japanese Journal of Hyperthermic Oncology, 2000)
The incidence of hepatocellular carcinoma is still gradually increasing in Japan. It is known that multiple hepatocellular carcinomas can occur simultaneously or at different times, and therapies of hepatocellular carcinomas including surgical hepatectomy, percutaneous ethanol injection therapy (PEIT), percutaneous acetic acid injection therapy (PAIT), percutaneous microwave coagulation therapy (PMT), and transcatheter arterial embolization therapy (TAE) result in prolongation of the patient's life. As a radical therapeutic method, surgical therapy is still recommended when the patient can tolerate it, though its incidence is getting lower than ever. To increase radical cure rate of PEIT among the non-surgical therapeutic methods for hepatocellular carcinoma, we developed percutaneous hot ethanol injection therapy, PHEIT and discussed its safety and usefulness.